German Mobile Apps in Rheumatology: Review and Analysis Using the Mobile Application Rating Scale (MARS) - Knitza, Johannes; Tascilar, Koray; Messner, Eva-Maria; Meyer, Marco; Vossen, Diana; Pulla, Almut; Bosch, Philipp; Kittler, Julia; Kleyer, Arnd; Sewerin, Philipp; Mucke, Johanna; Haase, Isabell; et al. (JMIR mHealth and uHealth, 2019)
Background: Chronic rheumatic diseases need long-term treatment and professional supervision. Mobile apps promise to improve the lives of patients and physicians. In routine practice, however, rheumatology apps are largely unknown and little is known about their quality and safety.
CRIS-Team WoS Importer:2019-08-27